Research on Dynamic Online Monitoring and Early Warning System for Mine Ventilation - Liang, Jun (Scientific Journal of Technology, 2025)
Coal mines in China primarily rely on manual methods for mine ventilation monitoring, which demands significant time, labor, and resources while offering low data real-time performance. An online ventilation network monitoring and early warning analysis software is developed. By integrating underground ventilation monitoring sensors, the system enables dynamic calculations of the ventilation network based on real-time underground changes. It provides clear and intuitive dynamic displays of airflow, wind speed, and other parameters in various tunnels on the ventilation system diagram. Additionally, it supports dynamic analysis of ventilation system reliability in underground tunnels, online monitoring of ventilation anomalies, and alarm functions. This system serves as a scientific management tool and advanced technological solution for mine ventilation safety management and safe production.